2004
DOI: 10.1136/gut.2003.025031
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the sensorimotor response to distension between the proximal and distal stomach in humans

Abstract: Background: It is not known which region of the stomach is responsible for symptom generation or whether symptoms induced by gastric distension are region specific. Also, it is unclear whether low level gastric distension has a modulatory role on gastric tone and mechanosensitivity. Aims: To define differences in the sensorimotor response to distension between proximal and distal gastric distension, and to determine the effects of low level gastric distension on gastric tone and mechanosensitivity. Methods: In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(49 citation statements)
references
References 20 publications
0
49
0
Order By: Relevance
“…1) Evidence is lacking that the antral wall is stretched or that there is a substantial increase in the antral slow-wave frequency after a meal. Other studies show that no differential intraluminal pressures are generated in different parts of the stomach after a meal, which does not support the differential stretches between the antrum and the corpus (95 2) The ICC-MY in the stomach have been proposed as pacemakers of the slow waves in the circular smooth muscle cells as well as the synchronizers of the regenerative potentials in the ICC-IM. It is not apparent how the signal generated by the mechanical stretch in the ICC-IM, can increase the pacemaker frequency of the ICC-MY, which would, in turn, increase the frequency of the slow waves in the circular muscle cells (11,71).…”
Section: Icc As Mechanosensorsmentioning
confidence: 92%
“…1) Evidence is lacking that the antral wall is stretched or that there is a substantial increase in the antral slow-wave frequency after a meal. Other studies show that no differential intraluminal pressures are generated in different parts of the stomach after a meal, which does not support the differential stretches between the antrum and the corpus (95 2) The ICC-MY in the stomach have been proposed as pacemakers of the slow waves in the circular smooth muscle cells as well as the synchronizers of the regenerative potentials in the ICC-IM. It is not apparent how the signal generated by the mechanical stretch in the ICC-IM, can increase the pacemaker frequency of the ICC-MY, which would, in turn, increase the frequency of the slow waves in the circular muscle cells (11,71).…”
Section: Icc As Mechanosensorsmentioning
confidence: 92%
“…35,40 Recent studies indicate that not only the proximal stomach but also, and maybe more intensely, the distal stomach may be involved in symptom generation due to gastric distension. [41][42][43][44] …”
Section: Hypersensitivity To Gastric Distensionmentioning
confidence: 99%
“…In studies using waterfilled balloon distension and positional changes, both antral and fundic hypersensitivity, as well as impaired duodeno-fundic and antro-fundic reflex activity were involved in symptom generation, and over-distension in the antrum was the most important site for symptom generation [30] . In a double antral and fundic barostat study, we showed that symptom profiles induced by gastric distention did not differ between proximal and distal gastric distension and that mechanoreceptors from both sites may contribute to symptoms [31] . Barostat and SPECT studies confirmed that meal ingestion also elicited antral relaxation [31,32] .…”
Section: Impaired Gastric Accommodation To a Mealmentioning
confidence: 83%